Efficacy and safety of apatinib monotherapy in advanced bone and soft tissue sarcoma: An observational study. Issue 3 (4th March 2018) - Zhu, Baorang; Li, Jing; Xie, Qiaosheng; Diao, Liyan; Gai, Lvhua; Yang, Wuwei
ABSTRACT: Sarcomas are rare but malignant tumors with high risks of local recurrence and distant metastasis. Anti-angiogenic therapy is a potential strategy against un-controlled and not-organized tumor angiogenesis. We aimed to assess the safety and efficacy of apatinib, an oral tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, in patients with advanced sarcoma. Thirty-one patients who received initial apatinib between September 2015 and August 2016 were retrospectively reviewed. Among them, 19 (61.3%) patients were heavily pretreated with two or more lines of cytotoxic chemotherapy. Apatinib was given at a start-dose of 425 mg qd. During therapy, 9 (29.0%) patients required dose interruption and 7 (22.6%) needed dose reduction, and the mean dosage of apatinib was 372.9 ± 68.4 mg/day. In the study cohort, one patient was treated as adjunctive therapy and 6 patients stopped treatment before radiographic response assessment. Thus, 24 patients were eligible for tumor response evaluation. The objective response rate was 33.3% and clinical benefit rate was as high as 75.0%. The progression free survival was 4.25 (95% confidence interval [CI], 2.22–5.11) months, whereas the overall survival was 9.43 (95% CI, 6.64–18.72) months. Compared with other histological subtypes, leiomyosarcoma did not show significant survival benefits. Most of the adverse events (AEs) were at grade 1 or 2. The main grade 3 AEs were hypertension (6.5%), hand foot skin reaction (6.5%), and diarrhea (3.2%). In conclusion, apatinib showed promising efficacy and acceptable safety profile in metastatic or recurrent sarcoma, giving rationale clinical evidence to conduct clinical trials.